2021
DOI: 10.1039/d0ra10039k
|View full text |Cite
|
Sign up to set email alerts
|

Upconversion luminescence and temperature sensing properties of NaGd(WO4)2:Yb3+/Er3+@SiO2 core–shell nanoparticles

Abstract: A shell of SiO2 with tunable thickness was uniformly coated on NaGd(WO4)2:Yb3+/Er3+ core upconversion nanoparticles (UCNPs). The effects of the silica shell on UC luminescence and thermal sensing properties of the core–shell UCNPs were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…The optical thermometry characteristics of the 4 S 3/2 and 4 F 9/2 levels are investigated here. Meanwhile, 4 S 3/2 and 4 F 9/2 levels belong to non-thermally coupled levels, and the FIR value of a non-thermally coupled level can be fitted by the following polynomial equation: 54,55 FIR = AT 3 + BT 2 + CT + D ,where A , B , C and D are fitting constants. According to eqn (5), the FIR values of SLF-E 8 NCs and SLF-E 8 /PAN composite fibers at 303−433 K were successfully calculated and are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The optical thermometry characteristics of the 4 S 3/2 and 4 F 9/2 levels are investigated here. Meanwhile, 4 S 3/2 and 4 F 9/2 levels belong to non-thermally coupled levels, and the FIR value of a non-thermally coupled level can be fitted by the following polynomial equation: 54,55 FIR = AT 3 + BT 2 + CT + D ,where A , B , C and D are fitting constants. According to eqn (5), the FIR values of SLF-E 8 NCs and SLF-E 8 /PAN composite fibers at 303−433 K were successfully calculated and are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…41–50 With the introduction of Er 3+ ions into crystals Sr 2 (La 1− x Er x )F 7 , composite fibers show both the pliability of fibers and the temperature transfer properties of Er 3+ ions, which provide the possibility of optical temperature sensing in microregions. 51–62…”
Section: Introductionmentioning
confidence: 99%
“…They showed that upon coating of the upconversion nanoparticles with a silica shell, the absolute sensitivity of the system increased almost two-fold with maximum S a = 1.03%/K at 350 K, and maximum S r = 1.10%/K at 300 K ( 2 H 11/2 / 4 S 3/2 ), as compared to maximum S a = 0.66%/K at 350 K, and maximum S r = 0.98%/K at 300 K for the bare NaGd(WO 4 ) 2 :Yb 3+ -Er 3+ ( 2 H 11/2 / 4 S 3/2 ), respectively. 108 Synthesis of multifunctional upconversion Gd 2 (WO 4 ) 3 :Yb 3+ -Ho 3+ @SiO 2 nanoparticles has been reported by Liu et al 109 They further functionalized the particles with cis,cis,transdiamminedichlorodisuccinatoplatinum(IV) drug or (DSP), and polyethylene glycol (PEG). Afterwards, the group investigated the temperature sensing properties of the Gd 2 (WO 4 ) 3 :Yb 3+ -Ho 3+ @SiO 2 -Pt-PEG under 980 nm excitation in the physiological range and subsequently exploited them for bi-modal upconversion fluorescence (UCL) and magnetic resonance (MR) imaging, as well as for in vitro and in vivo investigation of the chemotherapeutic activity of the platinum(IV) drug in comparison with cisplatin.…”
Section: Temperature Sensingmentioning
confidence: 98%
“…They showed that upon coating of the upconversion nanoparticles with a silica shell, the absolute sensitivity of the system increased almost two-fold with maximum S a = 1.03%/K at 350 K, and maximum S r = 1.10%/K at 300 K ( 2 H 11/2 / 4 S 3/2 ), as compared to maximum S a = 0.66%/K at 350 K, and maximum S r = 0.98%/K at 300 K for the bare NaGd(WO 4 ) 2 :Yb 3+ -Er 3+ ( 2 H 11/2 / 4 S 3/2 ), respectively. 108…”
Section: Some Notable Advances For In Vitro and In Vivo Investigation...mentioning
confidence: 99%
“…In general, the coating of the nanocrystals with a SiO 2 shell is considered as a common approach to minimize the surface-related quenching effects on the luminescence. , The implementation of a silica shell is based on its unique properties, including high thermal and chemical stability, optical transparency, and easy control of the coating shell . In addition, SiO 2 compounds may act as binders for phosphors, together forming paints dedicated for temperature measurements in aerospace applications reaching 1000 °C. , On the other hand, the biocompatibility of the SiO 2 shell and its further functionalization with versatile organic and inorganic compounds are crucial for its biological applications as well as for enabling the nanoparticle dispersion in polar and nonpolar environments. In addition, the use of porous silica shells can extend the range of applications to include targeting binding, such as drug delivery …”
Section: Introductionmentioning
confidence: 99%